Competitive Influence Maximization in Social Networks - Kamble, SS; Bagban, TI (International Journal of Computer Sciences and Engineering, 2025)
Impact amplification is aware of augment the good thing about infective agent promoting in informal organizations. The defect of impact growth is that it does not acknowledge specific shoppers from others, despite the likelihood that some things are often useful for the actual shoppers. For such things, it's a superior system to consider boosting the impact on the actual shoppers. During this paper, we tend to detail an effect boost issue as question handling to acknowledge specific shoppers from others. We tend to demonstrate that the question handling issue is NP-hard and its target capability is sub secluded. We tend to propose a need model for the estimation of the target capability and a fast covetous primarily based shut estimation strategy utilizing the need model. For the need model, we tend to explore a relationship of the way between shoppers. For the covetous technique, we tend to estimate a productive progressive overhauling of the negligible addition to our goal capability. We tend to lead trials to assess the planned technique with real datasets, and distinction the outcomes and people of existing systems that area unit adjusted to the problem. From our trial results, the planned strategy is not any but asking of extent speedier than the prevailing routines by and enormous whereas accomplishing high truth. Also we are implementing Maximum Coverage algorithm in which will post or spread add(product list) as per category wise means we will divide the age category in different age group range by using Maximum Coverage algorithm and that particular adds will be displayed to particular age group users. This allows the marketers to plan and evaluate strategies online for advertised products.